Simulation of tempering drying of porous media based on COMSOL multi-physics field - LIU Dingtong; LIU Zeyu; LIU Shaodong; FENG Tai (Shipin yu jixie)
ObjectiveTo investigate the variation laws of temperature and humidity fields during the tempering process.MethodsUsing corn kernels and grain piles as porous media, perform multi-physics field coupling using the heat and moisture flow interface in the COMSOL Multiphysics heat transfer module.ResultsFive tempering and six drying processes reduced the relative humidity of corn kernels from 22.5% to 4.97%, and after two tempering and three drying processes, the average relative humidity of corn kernels decreased to 11%. The drying effect improved by 9.5% compared to no tempering drying. The same effect was obtained by the strategy of tempering at normal temperature with less drying time.ConclusionThe tempering strategy effectively improves he drying rate by reducing the moisture gradient, shortening the overall hot air drying time. However, the drying and slow fermentation times are increased. The application of ambient temperature ventilation slow fermentation strategies in the air-drying chamber can further reduce the number and duration of slow fermentation sessions required in the later stages of drying.